Perampanel and Visuospatial Skills in Children With Epilepsy - Operto, Francesca Felicia; Vivenzio, Valentina; Scuoppo, Chiara; Padovano, Chiara; Roccella, Michele; Quatrosi, Giuseppe; Pastorino, Grazia Maria Giovanna (Frontiers in Neurology, 2021)
Introduction: Perampanel (PER) is a non-competitive AMPA glutamate receptor antagonist approved for focal and generalized seizures as add-on therapy. PER does not seem to negatively affect the cognitive profile in children and adolescents, but its influence on visuospatial abilities is still to be assessed. The aim of our study was to asses visuospatial skills, through a standardized neuropsychological evaluation, in adolescents taking PER for 12 months. Methods: Our sample included 46 adolescents aged 12-18 years, with focal and generalized drug-resistant epilepsy, already in therapy with 1 or 2 antiseizure medications. Changes in visuospatial perception and memory were assessed by Rey-Osterrieth Complex Figure Test at baseline (before taking PER) and after 12 months of pharmacological treatment. Executive functions and non-verbal intelligence were also assessed at baseline. Results: After 12 months of PER therapy the mean scores of Rey-Osterrieth Complex Figure Test remained almost unchanged, both for visuospatial perception and for visuospatial memory skills. At baseline visuospatial memory was related to executive functions, while visuospatial perception was related to executive function and non-verbal intelligence. Conclusions: Adjunctive treatment with PER did not negatively affect visuospatial skills. No adverse events effects have been reported after 12 months follow-up, and this suggests a good tolerability in the middle/long term.